Repair of critical size defects using bioactive glass seeded with adipose-derived mesenchymal stem cells - YILMAZ, BETÜL; SAÇAK, BÜLENT; ERCAN, FERİHA; ÖZKAN YENAL, NAZİYE; ÇELEBİLER, ÖZHAN BEKİR; AKDENİZ DOĞAN, ZEYNEP DENİZ (WILEY, 2017)
Bioactive glass has been demonstrated as a biocompatible bone substitute. However bone healing process can be prolonged due to late resorption of the material. Adipose derived stem cells (ASC) have osteogenic differentiation potential and hence can be a cell source for bone regeneration. The aim of this study was to test whether combination of bioactive glass with ASCs would enhance bone regeneration. Following creation of critical sized defects on the calvaria of 32 Wistar rats, the animals were randomly divided into four groups: Group C (control): Defects were left untreated; Group G: Defects were covered with autologous bone graft; Group BG: Defects were filled with bioactive glass; Group BG/ASC: Defects were filled with bioactive glass seeded with ASCs. The defect size was significantly greater in Group compared to all other groups. Bone density was significantly lower in Group C compared to Group G and Group BG/ASC. Bone regeneration score of Group C was significantly lower than other groups. Group BG/ASC demonstrated lamellar bone and havers canal formation. The results of this study demonstrated that bioactive glass implanted with ASC is a biocompatible construct stimulating radiologically and histologically evident bone regeneration similar to autologous bone grafting. (C) 2016 Wiley Periodicals, Inc.
Keywords: bioactive glass; adipose derived stem cell; bone regeneration; critical size defect; ORBITAL FLOOR FRACTURES; CALVARIAL DEFECTS; BONE DEFECTS; AUTOGENOUS BONE; STROMAL CELLS; IN-VIVO; RECONSTRUCTION; TISSUE; AUGMENTATION; REGENERATION